Celebrated Econometricians: Katarina Juselius and Søren Johansen - Mosconi, Rocco; Paruolo, Paolo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue collects contributions related to advances in the theory and practice of Econometrics induced by the research of Katarina Juselius and Søren Johansen, whom this Special Issue aims to celebrate. The papers in this Special Issue provide advances on several topics, and they are grouped in the following areas, with three to four papers per group). The first group provides a historical perspective on Katarina's and Søren's contributions to Econometrics. The second group of papers concentrates on representation theory, while the third focuses on estimation and inference. The fourth group explores extensions of CVARs for modelling and forecasting, and the fifth and final group is centered on empirical applications.